2014
DOI: 10.5395/rde.2014.39.3.187
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bone morphogenetic protein-2 and enamel matrix derivative on the bioactivity of mineral trioxide aggregate in MC3T3-E1cells

Abstract: ObjectivesThe effects of bone morphogenetic protein-2 (BMP-2) and enamel matrix derivative (EMD) respectively with mineral trioxide aggregate (MTA) on hard tissue regeneration have been investigated in previous studies. This study aimed to compare the osteogenic effects of MTA/BMP-2 and MTA/EMD treatment in MC3T3-E1 cells.Materials and MethodsMC3T3-E1 cells were treated with MTA (ProRoot, Dentsply), BMP-2 (R&D Systems), EMD (Emdogain, Straumann) separately and MTA/BMP-2 or MTA/EMD combination. Mineralization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Among them, BMP-2 is the most effective inducer of proliferation, differentiation, and mineralization in osteoblasts (Higuchi et al, 2002, Hiraki et al, 1991). Previous studies have shown that MTA promoted osteoblastic mineralization concomitant with increased BMP-2 mRNA expression (Ghasemi et al, 2014, Jeong et al, 2014). Here, we also investigated MTA-induced osteoblastic mineralization without BMP-2 mRNA elevation compared to controls.…”
Section: Discussionmentioning
confidence: 91%
“…Among them, BMP-2 is the most effective inducer of proliferation, differentiation, and mineralization in osteoblasts (Higuchi et al, 2002, Hiraki et al, 1991). Previous studies have shown that MTA promoted osteoblastic mineralization concomitant with increased BMP-2 mRNA expression (Ghasemi et al, 2014, Jeong et al, 2014). Here, we also investigated MTA-induced osteoblastic mineralization without BMP-2 mRNA elevation compared to controls.…”
Section: Discussionmentioning
confidence: 91%
“…However, the varying ratio of the growth factors mobilized by MTA affects the nature of the tissue repair. In this regard, there have been several attempts at combining MTA with factors such as fibroblast growth factor‐2, bone morphogenetic protein‐2 (BMP‐2) and enamel matrix derivative, respectively . While these have been successful in enhancing the proliferation and differentiation of pulpal cells, at times, an unfavorable relationship between the released growth factors and the extracellular matrix exists which results in apoptosis (instead of repair).…”
Section: Endodontic Materialsmentioning
confidence: 99%
“…In this regard, there have been several attempts at combining MTA with factors such as fibroblast growth factor-2, bone morphogenetic protein-2 (BMP-2) and enamel matrix derivative, respectively. [48][49][50] While these have been successful in enhancing the proliferation and differentiation of pulpal cells, at times, an unfavorable relationship between the released growth factors and the extracellular matrix exists which results in apoptosis (instead of repair). In addition, these cell death pathways are also activated at high concentrations of MTA (200 mg/mL).…”
Section: 2637mentioning
confidence: 99%
“…One microgram RNA was reverse-transcribed with oligo (dT) 15 primers by using AccuPower RT PreMix (iNtRON Biotechnology, Gyeonggi-do, South Korea). Next, the generated cDNAs were amplified with AccuPower PCR PreMix (Bioneer Corporation, Daejeon, South Korea).…”
Section: Rna Isolation and Reverse Transcriptase Polymerase Chain Reamentioning
confidence: 99%
“…Moreover, we demonstrated that a combination of MTA and enamel matrix derivative promoted more rapid differentiation in HDPCs, as compared with pure MTA (14). In addition, the MTA/bone morphogenetic protein-2 (BMP-2) combination promoted more rapid differentiation in MC3T3-E1 cells than did MTA or enamel matrix derivative alone (15). MTA mixed with hydration accelerators such as calcium chloride and low-dose citric acid more upregulated osteogenic genes than that of MTA alone in mouse osteoblasts (5).…”
mentioning
confidence: 94%